Implementasi Strategi Pembelajaran dalam Mengembangkan Pemahaman Aqidah Akhlak pada Siswa SD Muhammadiyah Ashabul Kahfi Program Khusus Sidoharjo Wonogiri - Lina Suratunnisa (Journal Islamic Education, 2024)
This study aims to analyze the learning strategies applied in developing students' understanding of aqidah and akhlak at Muhammadiyah Ashabul Kahfi Elementary School, Special Program, Sidoharjo, Wonogiri. This study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results of the study indicate that the learning strategies applied at Muhammadiyah Ashabul Kahfi Elementary School, Special Program, Sidoharjo, Wonogiri include a contextual, active approach, and are based on Islamic values integrated into the curriculum. Learning is carried out through lectures, discussions, and direct practice in daily life. Students' understanding of aqidah and akhlak increased significantly with the application of varied methods, as well as support from an environment that supports strengthening Islamic character. Overall, the results of this study indicate that the implementation of appropriate learning strategies can improve students' understanding of aqidah and akhlak, which is reflected in their attitudes and behaviors that are more in accordance with Islamic teachings. Based on this, the author is very interested in examining more deeply the learning strategies applied in developing students' understanding of aqidah and akhlak. This study found that the implementation of appropriate learning strategies, supported by a contextual approach and based on Islamic values, can effectively improve the understanding of the aqidah and akhlak of students at SD Muhammadiyah Ahabul Kahfi Special Program Sidoharjo Wonogiri.